The Influence of Institutional Ownership, Independent Commissioners, Independent Directors, and Philanthropy on Firm Value - Christina Dwi Astuti; Clarissa Audrey Sanggra; Murtanto Murtanto (Green Publisher Indonesia, 2022)
This research aims to examine the effect of institutional ownership, independent commissioners, independent directors and philanthropy on firm value. The population in this study is the IDX classification industry start-up listed on the Indonesia Stock Exchange (IDX) from 2018 to 2020. The type of data used is financial reports and annual reports of 76 companies using the purposive sampling method. Furthermore, the analytical model used in this study is multiple linear regression analysis. Based on the results of the analysis obtained from this study, it is concluded that institutional ownership, independent commissioners and philanthropy have no effect on firm value, but independent directors have a positive effect on firm value